EFFICACY OF USING A SPECIAL APPLICATOR ON MUSCLE RECOVERY DURING AND AFTER EXERCISE IN SHORT, MIDDLE AND LONG DISTANCE RUNNERS (Scientific journal of the Fergana State University, 2024)
This article provides information on the effectiveness of using a special applicator for muscle recovery during and after training in short, medium and long distance runners.